ARTIFICIAL INTELLIGENCE-ASSISTED FEEDBACK IN ACADEMIC WRITING: STUDENTS’ EXPERIENCES, BENEFITS, AND CHALLENGES IN HIGHER EDUCATION - Juliati Juliati; Azrul Rizki (Sensei International Journal of Education and Linguistic, 2024)
Nowadays many students use artificial intelligence to help them in writing. This is because artificial intelligence can give feedback very fast and can be accessed any time. This study discusses artificial intelligence-assisted feedback in academic writing and the experiences of the students. The study used a mixed-method design. The data were collected through a questionnaire, interviews, and analysis of students' writing drafts. The data were analyzed descriptively and thematically. The result of the study shows that the students have a positive perception of artificial intelligence feedback, especially for grammar, but they also have some problems such as feeling too dependent and being confused about whether it is allowed or not. Therefore, lecturers should guide the students in using artificial intelligence in academic writing.